Derivational-interpretative Process and Its Consequences, while Explaining Linguistic Phenomena in the Russian Language System - Надежда Николаевна Шпильная (Philology & Human, 2019)
The author of the article offers a new concept of language as an interpretative-derivational mechanism, which determines the interaction of tendencies to interpretability and reproduction / production of linguistic signs.The subject of the research is derivational-interpretative process and its consequences, while explanation of linguistic phenomena in the Russian language system take place. The derivational-interpretative process is believed to neutralize the language and speech opposition. At the same time, the transition from language to speech is carried out due to the interpretation mechanism which correlates with the rules of transformation of language units and / or with the pragmatic focus of a native speaker, actualizing various emotional connotations of language units.The article analyzes the consequences of the derivational-interpretative process at the phonetic (phonological), lexical, derivational, morphonological, morphological, syntactic and textual levels of the language system.